Survival of Dwarf Gourami (Colisa Lalia, Hamilton–Buchanan, 1822) Embryos after Incubation in Cryoprotective Media - Mikson, K. B.; Kopejka, Ye. F.; Linnik, T. P. (Problems of Cryobiology and Cryomedicine, 2008)
The influence of cryoprotectants on survival rate of Calisa lalia at stage before hatching was studied. It was found that the composition and incubation temperature significantly influenced the embryonic development; incubation for 30 minutes at 2°С led to significant teratogenic alterations in ontogenesis of both control and cryoprotectant-treated experimental groups as well; incubation of embryos at 28°С with cryoprotective media, containing 1 M sucrose and 1.32 М ethylene glycol did not lead to significant decrease in survival rate and appearance of abnormally developing embryos; embryos incubation for 15 min with N-acetyl ethanolamide, N,Ndimethylformamide and formamide in concentration of 0.96, 0.8 and 1.87М, correspondingly led to the increase of mortality level and therefore the use of these cryoprotectants necessitated an additional study.